2017
DOI: 10.1007/s13361-017-1649-4
|View full text |Cite
|
Sign up to set email alerts
|

Radical Generation from the Gas-Phase Activation of Ionized Lipid Ozonides

Abstract: Reaction products from the ozonolysis of unsaturated lipids at gas–liquid interfaces have the potential to significantly influence the chemical and physical properties of organic aerosols in the atmosphere. In this study, the gas-phase dissociation behavior of lipid secondary ozonides is investigated using ion-trap mass spectrometry. Secondary ozonides were formed by reaction between a thin film of unsaturated lipids (fatty acid methyl esters or phospholipids) with ozone before being transferred to the gas pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
(70 reference statements)
3
14
1
Order By: Relevance
“…This peak was reported by Reis et al 76 , based on the oxidation of POPC lipids by hydroxyl radicals during Fenton reaction and involving a Hock rearrangement. Moreover, Ellis et al 78 observed similar peaks after ozonolysis of unsaturated lipids based on Criegee mechanism of alkene ozonolysis (Fig. 8 ).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…This peak was reported by Reis et al 76 , based on the oxidation of POPC lipids by hydroxyl radicals during Fenton reaction and involving a Hock rearrangement. Moreover, Ellis et al 78 observed similar peaks after ozonolysis of unsaturated lipids based on Criegee mechanism of alkene ozonolysis (Fig. 8 ).…”
Section: Resultssupporting
confidence: 52%
“…
Figure 8 Suggested products of peak at m/z = 830.55 with addition of three oxygen atoms in lipid structure after plasma treatment and subsequent rearrangements (Hock cleavage, homolytic β-scission, etc.) lead to stable products such as aldehydes (PoxnoPC) 76 , 78 80 .
…”
Section: Resultsmentioning
confidence: 99%
“…A hypothetical mechanism is provided that describes unimolecular H-shifts of the SCI to form these C 10 H 15 O 4 · isomers (Figure S20). These “long-range” H-shifts appear to be unfavored by the strained cyclobutyl ring, but similar mechanisms have been proposed in prior studies to explain the formation of pinonic acid and pinic acid. , Another plausible mechanism derived from the SOZ was also shown (Figure S22) to form the C 10 H 15 O 4 · that leads to pinic acid . But if this is indeed the mechanism for our observation, it is possible that with the lower energy distributed to the CIs in the ozonolysis of CI k -enone and CI a -enal than that in actual α-pinene ozonolysis, the fraction of common products between the two CI pathways could have been overestimated.…”
Section: Results and Discussionsupporting
confidence: 83%
“…This indicates that the vinyl hydroperoxide structures are unlikely as these have previously been shown to undergo facile oxidative cleavage of the carbon-carbon double bond under similar conditions in the gas phase (Vu et al, 2017). At the same time CID of the +48 adduct ions results principly in even-electron product ions, which contrasts with our previous investigations of the unimolecular dissociation of secondary ozonides (Ellis et al, 2017). Rather the spectra in Figure 3A and B both show abundant product ions resulting from consecutive losses of stearic acid and carbon dioxide (i.e., m/z 379 and m/z 395, respectively).…”
Section: Gas Phase Ozonolysis Of Ionised Cholestanyl Oleate and Cholecontrasting
confidence: 76%